Early posttherapy clearance of human papillomavirus and treatment response in cervical carcinoma. Issue 18 (8th July 2020) - Srivastava, Amar J.; Contreras, Jessika A.; Davis, Melanie; Markovina, Stephanie T.; Schwarz, Julie K.; Grigsby, Perry W.
Abstract : Background: Among patients with cervical cancer, little is known about the significance of persistent human papillomavirus (HPV) expression after chemoradiation (CRT). This study evaluated associations between early posttreatment HPV clearance and patient outcomes with an added focus on the value of posttherapy positron emission tomography (PET) imaging. Methods: Included patients underwent pretreatment testing indicating a high‐risk HPV infection and posttreatment testing with a messenger RNA (mRNA)–based genital swab after CRT. Posttherapy responses were stratified on the basis of HPV mRNA detection into an early clearance (EC) group (no mRNA) and a persistent expression (PE) group (detectable mRNA) on the basis of an evaluation at a median of 6 weeks after therapy. The Kaplan‐Meier method was used to compare outcomes, and multivariable analysis was used to identify predictors of outcomes. Results: Seventy‐two of the 97 eligible patients (74.2%) had EC. The mean follow‐up time was 25 months (range, 4‐56 months), and 2‐year pelvic control (76.9% vs 50.2%; P  = .01) and overall survival (OS; 80.9% vs 52.2%; P  < .01) were superior among EC patients. In the multivariable analysis, EC predicted for improved survival (hazard ratio [HR] for mortality, 0.46; 95% confidence interval [CI], 0.21‐0.96; P  = .047), as did a complete response (CR) on posttherapy PET (HR for less than a CR on PET, 6.17; 95% CI, 2.58‐14.72; P  < .01). In a subset analysis of patients with a posttherapy PET CR, HPV clearance retained prognostic significance (2‐year OS, 95.6% with EC vs 66.7% with PE; P  = .04), whereas PE patients without a PET CR had the worst survival (35.9%; P  < .01 for trend). Conclusions: Early posttherapy clearance of HPV is associated with improved survival in cervical cancer. Evaluating HPV expression at this 6‐week time point provides prognostic information beyond posttherapy PET imaging and may aid in risk stratification and decisions for treatment escalation. Abstract : In this study of patients with cervical cancer, persistent expression of human papillomavirus (HPV) 6 weeks after the completion of definitive chemoradiation is independently associated with a poor prognosis, and the posttherapy HPV clearance status retains prognostic significance even in patients with posttherapy positron emission tomography (PET) showing a complete metabolic response. Pending prospective validation, these findings suggest that the posttherapy HPV status with PET imaging could be used for decisions regarding surveillance, risk stratification, and treatment escalation.